Analisa Kinerja Relay Differensial pada Gardu Induk Surabaya Selatan Sebagai Sistem Proteksi dari Gangguan Arus Hubung Singkat Transformator Menggunakan Metode Algoritma Genetik - Misbahul Munir; Nasyith Hananur Rohiem; Wahyu Setyo Pambudi; Novian Patria Uman Putra; Echwan Muliyana (STMIK Budi Darma, 2023)
One of the disturbances in the transformer at the South Surabaya Substation is a short circuit, this disturbance causes an increase in the flow of electric current to a large extent resulting in heat on the transmission line and damage to the electric power system equipment so protection is needed. One type of equipment that needs to be protected is a transformer using a differential relay. In this study, the process of determining the relay settings was used using a numerical process and compared with the genetic algorithm(AG)method. In the AG process, the targeted optimization values are the current values of IsettandId. The results of the two processes are compared with the existing conditions to determine the resulting acceleration of the trip relay response. The trip response acceleration of each differential relay from the AG results shows an acceleration value of 0.088s, 0.047s, and 0.047s to the existing conditions while the numerical process shows an acceleration of the trip process of 0.083s, 0.045s, and 0.045s to the existing conditions. The results of the AG optimization show that the acceleration response is the best compared to the numerical process